Remimazolam used for sedation during spinal anesthesia puncture provides faster sedation effect and increase recovery rate compared to midazolam: a randomized controlled trial - Sun, Peipei; Tan, Zhimin; Liang, Lianxiong; Zhang, Jianbo; Li, Xiaoqiang (Frontiers in Pharmacology, 2025)
BackgroundSurgical time-out is essential for patient safety, requiring patients to remain conscious to verify their identity and surgical site. In China’s high-volume operating rooms, this step is crucial to prevent errors. Spinal anesthesia often induces anxiety, making sedation necessary. An ideal sedative must provide effective anxiolysis while allowing rapid recovery. This study compares remimazolam and midazolam to meet these dual demands and assess their cardiorespiratory safety.MethodsThis prospective, randomized controlled trial compared remimazolam and midazolam for sedation in patients undergoing elective ultrasound-guided spinal anesthesia. Patients were assigned to receive either remimazolam (0.1 mg/kg bolus, 0.5–1.0 mg/kg/h infusion) or midazolam (0.07 mg/kg bolus, 0.05–0.1 mg/kg/h infusion). Sedation was titrated to a target Richmond Agitation–Sedation Scale (RASS) score of −4. The primary outcome was the recovery time from RASS –4 to −1. Secondary outcomes included onset time, hemodynamic changes, respiratory parameters, and presences of adverse events.ResultsOf the 103 patients screened, 56 were eligible and randomized into the remimazolam (n = 28) and midazolam (n = 28) groups. The sedation onset time [1.5 (1.0, 2.0) min vs. 3.1 (2.8, 5.0) min, P < 0.001] and recovery time [3.9 (3.0, 5.2) min vs. 6.1 (3.1,10.0) min, P = 0.0016] was significantly shorter in the remimazolam group than midazolam group. Remimazolam had no significant impact on procedural time of ultrasound-guided spinal anesthesia. Both groups showed significant within-group decreases in mean arterial pressure during sedation (remimazolam: from 81.5 to 75 mmHg; midazolam: from 81.7 to 72.4 mmHg; P < 0.05), with no significant inter-group difference. At end of the procedure, remimazolam group had a higher respiratory rate than midazolam group (18.6 ± 3.3 vs. 16.8 ± 2.8) (P < 0.05). No significant differences were observed in heart rate, end-tidal carbon dioxide partial pressure, and oxygen saturation between groups. Remimazolam was not associated with an increased risk of adverse events.ConclusionRemimazolam demonstrated superior recovery in sedation depth, with a significantly shorter time to regain consciousness (RASS –4 to −1), compared with midazolam in patients undergoing ultrasound-guided spinal anesthesia. No significant differences in circulatory or respiratory parameters were observed between groups, though the study may lack power to detect minor safety effects.